The Position of Agreements Made by Minors in Game Top-Up Transactions as Reviewed by Law Number 1 of 2024 Concerning Electronic Information and Transactions - Aswandi Humonggio; Nirwan Junus; Nurul Fazri Elfikri (Fox Justi : Jurnal Ilmu Hukum, 2026)
This study analyzes the position of agreements made by minors in game top-up transactions, as reviewed by Law Number 1 of 2024 concerning Electronic Information and Transactions (ITE Law) and the Civil Code (KUHPerdata), amidst the rise of digital transactions involving legally incompetent parties, such as the UniPin case worth IDR 800,000. The problem formulation focuses on the formal validity of electronic contracts based on Article 18 paragraph (1) of the ITE Law versus the substantive requirements of legal competence (Article 1320 in conjunction with Article 330 of the Civil Code), with the aim of examining the implications of the vernietigbaar agreement. This research is normative juridical in nature, using a legislative and conceptual approach, with primary data sources in the form of the ITE Law, the Civil Code, and the Child Protection Law No. 35 of 2014; secondary data includes civil law literature, journals, and platform documents. Data collection was conducted through a literature study of the BPHN and JDIH databases, analyzed qualitatively and descriptively using the legal weight method to assess the hierarchy of norms. The results of the study show that digital agreements by minors are formally valid but subjectively flawed, so they can be canceled by guardians through the courts for restitutio in integrum. The conclusion recommends age verification and parental consent regulations on PSEs to synchronize cyber-civil law.